Behavioral, Emotional, and Social Difficulties of Children and Adolescents With Dyslexia and Developmental Speech and Language Disorders - Milićević, Milena; Milošević, Neda (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
The authors have tried to present behavioral, emotional and social difficulties of children and adolescents with dyslexia and with developmental disorders of speech and language abilities, through a brief review of the research of behavioral profiles of children and their mental difficulties, primarily of emotional and social nature. Research literature indicated that children with specific language impairment and speech disorders, as well as children with reading disorders, or dyslexia, were at increased risk of behavioral disorders. A wide range of detected problems was confirmed, with differences found in relation to informants. Findings of the dominant representation of externalizing versus internalizing symptomatology of behavioral problems in children from these populations were contradictory. Longitudinal findings indicated that the direction of impact might be from language abilities to behavior. Therefore, a behavioral profile should be an integral part of the diagnostic assessment of children with language and/or speech disorders. Similarly, the treatment of language abilities should be an essential part of both preventive programs and the treatment of attention deficit and externalizing behavioral problems.